Examining the Efficacy of E-Service-Learning - Figuccio, Michael J. (Frontiers in Education, 2020)
E-service-learning is a pedagogical technique in which instruction and/or service occur online. Students in a distance learning section of Atypical Development course created a Google Site with resources for individuals with developmental disabilities. Additionally, students met with youths with developmental disabilities biweekly via Blackboard Collaborate Ultra sessions. At the end of the semester, students completed a questionnaire assessing their e-service-learning experience. Students reported that the e-service-learning experience was related to course content, increased their understanding of individuals with disabilities, increased student engagement, helped them relate the subject matter to everyday life, positively impacted their future academic and career choices, and overall had a positive experience. Students in a face-to-face section of Atypical Development who completed an in-person service-learning project did not significantly differ on any of the aforementioned measures. Course evaluations were also examined for both sections. Students in the e-service-learning section reported greater satisfaction than the in-person service-learning course. Specifically, e-service-learning students reported: the instructor attempted to make the course relevant to students; the assignments helped me learn the subject matter; I enjoyed the class greater than students in the in-person service-learning course. These results indicate that e-service-learning is an efficacious pedagogical practice in distance learning courses.